Geology of the recently discovered massive and stockwork sulphide mineralization at Semblana, Rosa Magra and Monte Branco, Neves-Corvo mine region, Iberian Pyrite Belt, Portugal - Pereira, Zélia (2021)
ABSTRACT: The recently discovered massive and stockwork sulphide mineralization of Semblana-Rosa Magra and Monte Branco, situated ESE of the Neves–Corvo volcanogenic massive sulphide (VMS) deposit in the Iberian Pyrite Belt (IPB) is presented. Geological setting and tectonic model is discussed based on proxies such as palynostratigraphy and U–Pb zircon geochronology. The mineralization is found within the IPB Volcano-Sedimentary Complex (VSC) Lower sequence, which includes felsic volcanic rocks (rhyolites) with U–Pb ages in zircons of 359.6 ± 1.6 Ma, and black shales of the Neves Formation of late Strunian age. Massive sulphides are enveloped by these shales, implying that felsic volcanism, mineralization and shale sedimentation are essentially coeval. This circumstance is considered highly prospective, as it represents an important exploration vector to target VMS mineralization across the IPB, in areas where the Lower VSC sequence is present. The Upper VSC sequence, with siliciclastic and volcanogenic sedimentary rocks of middle–late Visean age, shows no massive mineralization but a late Tournaisian (350.9 ± 2.3 Ma) volcanism with disseminated sulphides was also identified. Nevertheless, stratigraphic palynological gaps were found within the Strunian and in the Tournaisian sediments, between the Lower and Upper VSC sequences, reflecting probable erosion and uplift mechanisms linked with extensional tectonics. The Semblana and Monte Branco deposits and the Rosa Magra stockwork are enclosed by tectonic sheets that dismembered the VSC sequence in a fold-and-thrust tectonic complex, characteristic of the NE Neves–Corvo region. The methodologies used allow a geological comparison between Neves–Corvo and other IPB mine regions such as Lousal–Caveira, Herrerias, Tharsis and Aznalcollar.